Meteorological Changes Across Curiosity Rover’s Traverse Using REMS Measurements and Comparisons Between Measurements and MRAMS Model Results - María Ruíz; Eduardo Sebastián-Martínez; Jose Antonio Rodríguez-Manfredi; Jorge Pla-García; Manuel de la Torre-Juarez; Scot C. R. Rafkin (Remote Sensing)
The Curiosity rover, from NASA’s Mars Science Laboratory (MSL), has climbed nearly 740 m from its landing location at −4500.971 m in Gale Crater to a location reached on sol 3967 on the slopes of Mt. Sharp at −3765.27 m. We examine the atmospheric pressure, surface and atmospheric temperatures, relative humidity, and water vapor volume mixing ratios from measurements made by the Rover Environmental Monitoring Station (REMS), taken along the trajectory traveled over 3967 sols spanning from late MY31 to mid-MY37, on an interannual scale. The results help us understand the Martian meteorology inside Gale Crater. The atmospheric pressure and temperature changes caused by the elevation variation of the rover show the impact of the altitude change on the atmospheric dynamics. Regarding the rover’s locations for MY32 and MY36, a detailed comparative analysis of the full diurnal cycle is performed for the solstices and equinoxes. These scenarios are examined using the REMS and the Mars Regional Atmospheric Modeling System (MRAMS) data. We compare the REMS and MRAMS data to evaluate their concordance. We present, for the first time, a hypothesis for the existence of the cold pool phenomenon, which also occurs on Earth, based on REMS data.